Exploring Antibiotic Use in the Community: A Household-Based Survey Using the Drug Bag Method in Rural Burkina Faso - Adélaïde Compaoré; Toussaint Rouamba; Bérenger Kaboré; Jan Jacobs; Koen Peeters Grietens; Salla Sariola (MDPI AG, 2024)
In Burkina Faso, there is lack of awareness of antibiotic use at the community level. This study aims to generate information on the commonly used antibiotics along with the reasons for which they have been used in rural Burkina Faso. The drug bag method was employed to collect information from 423 households in the health district of Nanoro. Descriptive analyses were performed using R software version 4.2.1. Of the 33 antibiotics inventoried, amoxicillin tablets and oxytetracycline were the most recognized and used antibiotics. This study indicated that antibiotics were used for a range of health problems in the community, some of which were administered as painkillers. While primary healthcare facilities constituted the primary source of drugs for households (76.8%), informal drug sellers constituted an additional option (61.5%) for community members. This is a significant concern, given that some antibiotics classified as "Watch"-such as norfloxacin-were readily available in these outlets, despite not being included on the country's Essential Medicines List. This study underscores the necessity of considering the role played by formal providers in the inappropriate use of antibiotics and the importance of understanding the circumstances and logical reasoning underlying communities' access to and use of antibiotics.